Factors affecting adoption of mulching in Kibaale sub-catchment, South Central Uganda - Kakaire, Joel; Mensah, Albert K.; Menya, Emmanuel (Int. J. Sustainable Agricultural Management and Informatics, 2016)
Mulching is one of the major soil and water conservation measures applied for conserving soil moisture and modifying soil physical environment. The study aimed at determining the factors which influence the adoption of mulching in Kibaale sub-catchment, Uganda. 100 structured questionnaires; key informant interviews and observation were used to obtain the socio economic and institutional data. To determine the factors affecting adoption of mulching, descriptive statistics and factor analysis were used. Chi-square (P ≤ 05) was used to establish the relationship between the identified factors and adoption. Using chi-square test, the study also identified Education level of household head, household size, accessibility to farmland and marital status as the major factors that significantly affected adoption of mulching. The community leaders should ensure that the members attain some level of education and ensure that the land owned by individuals is within their periphery of management and control.
Keywords: adoption; mulching; factor analysis; Kibaale sub-catchment; Uganda.